The Optimization of Quranic Reading And Writing: A Blended Learning Method On The Qur'an & Hadith Course At Min (State Islamic Elementary School) In Metro City, Lampung - Ahmad Zumaro (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
As the number of COVID-19 spreads shrinks, the government encourages face-to-face and online learning methods, commonly known as blended learning. The purpose of this research is to investigate how to optimize the blended learning approach and how the blended learning method affects the students' reading and writing skills of the Quran at MIN (State Islamic Elementary School) in Metro City, Lampung. The author employed qualitative and quantitative methodologies (mixed method) in the form of a sequential exploratory design to produce clearer and more accurate results. The researcher employed a closed interview triangulation approach to assessing the qualitative data, while the quantitative data analysis used statistical formulas using the questionnaire data and the results of the Quran reading and writing test. The samples taken for this research were fourth-grade students. Based on the study's findings, it is possible to infer that the blended learning method has been properly applied in each school by Quran & Hadith course teachers and that this method has a substantial influence on the literacy skills of MIN students in Metro City.